2018
DOI: 10.3892/or.2018.6247
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of type II alveolar epithelial cells induces reactivation of dormant tumor cells by enhancing TGF-β1/SNAI2 signaling

Abstract: Dormant tumor cells (DTCs) serve a crucial role in the pathogenesis of metastasis and may compromise the efficacy of existing therapeutic modalities aimed at fully eradicating cancer. However, the mechanisms underlying the dormant-to-proliferating switch of DTCs remain largely unknown. The lung is one of the most common sites of metastatic recurrence. The transdifferentiation of alveolar epithelial cells II (AEC IIs) to AEC Is is a hallmark of alveolar epithelial stimulation. However, the role of AEC II transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…PCGF2 is a chromatin-modifying protein that inhibits EMT and negatively regulates stem cell-like properties [ 195 , 196 ]. SNAI proteins play a crucial role in EMT and in repressing the mesenchymal-epithelial transition, being important in embryonic and tumor development [ 197 , 198 , 199 ]. On the other hand, a complex of SNAI and ID2 inhibits EMT [ 200 , 201 ].…”
Section: Regeneration After Anterior Eviscerationmentioning
confidence: 99%
“…PCGF2 is a chromatin-modifying protein that inhibits EMT and negatively regulates stem cell-like properties [ 195 , 196 ]. SNAI proteins play a crucial role in EMT and in repressing the mesenchymal-epithelial transition, being important in embryonic and tumor development [ 197 , 198 , 199 ]. On the other hand, a complex of SNAI and ID2 inhibits EMT [ 200 , 201 ].…”
Section: Regeneration After Anterior Eviscerationmentioning
confidence: 99%
“…SNAI proteins play a crucial role in the epithelial-mesenchymal transition (EMT) and in repressing the mesenchymal-epithelial transition (MET), being important in embryonic and tumour development [43][44][45] . The co-expression of Ef-snai2 and Ef-id2 (see below) may indicate partial involvement of the EMT mechanisms in the transformation of coelomic epithelial cells into enterocytes in E. fraudatrix.…”
Section: Search Of the Most Likely Candidates For The Role Of Transdimentioning
confidence: 99%
“…In the alveolar epithelium, the initial repair process is re-epithelialization of the denuded basement membrane and reassembly of tight junctions. This is accomplished primarily by type II alveolar epithelial cells, which are relatively resistant to injury [213] , [214] , [215] , [216] , [217] , [218] . Type II cells spread, proliferate, and transdifferentiate into type I cells to restore normal alveolar structure and barrier function [213] .…”
Section: The Respiratory Epithelium – Injury and Repair During Iav Inmentioning
confidence: 99%
“…Type II cells spread, proliferate, and transdifferentiate into type I cells to restore normal alveolar structure and barrier function [213] . Various signaling pathways have been identified that promote type II cell spreading [219] , [220] , proliferation [214] , [221] , and trans-differentiation [218] , [222] . A recent study shows that a subset of type II alveolar epithelial that is specifically responsive to Wnt and Fgf signalling may be the dominant progenitor cells during injury in mouse and humans [223] .…”
Section: The Respiratory Epithelium – Injury and Repair During Iav Inmentioning
confidence: 99%